RESULTS OF THE SURVEY OF OPINION IN THE INTENTION TO VOTE IN MUNICIPAL AND PRESIDENTIAL ELECTIONS TO STUDENTS OF THE UNMSM - Solano Dávila, Olga (2011)
In the present work, we present the results of the opinion poll of voting intentions of the students of San Marcos University in municipal elections of 2010 and presidential elections of 2011. We used stratified random sampling with allocation proportional to size (Scheffer y Mendenhall, 2007) and considered the following layers: Faculty of Administrative Sciences, Faculty of Biological Sciences, among others, in total twenty faculties of San Marcos University. The surveys were carried out in three stages, during the months of July, August and September. At each stage was considered to 500 participants who were selected from each of the twenty faculties, following the stratified sampling scheme with proportional allocation. o calculate the sample size was considered a limit to the estimation error of 4.41% with a confidence level of 95% and the information provided by the Unified Registration System (SUM) of students matriculated the first semester of 2010academic year. (Solano et al. 2011a).